Formulation of Paint using Natural Pigment from Lawsonia Inermis Leaves - Y. Abba, Z.; M.Gumel, S.; A.Idris, A.; A.Ibrahim, M. (International Journal of Advanced Chemistry, 2020)
The increased application of paint in coating industry for interior and exterior decoration and corrosion inhibition, has inspired research in paint formulations. However, due to the toxic effect of preparatory chemicals used in paints, and the restrictive environmental legislation, research efforts have been directed to a more green process. In this work colouring matter from Lawsonia inermis leaves were extracted using water and analyzed by TLC and FTIR spectroscopy. White emulsion paint was formulated using pigment volume concentration (PVC) of 0.07%, the colouring matter extract was dispersed providing colour for the paint. The paint produced with the natural colourant was found to have similar properties with the paint produced using commercial pigment. Paint produced with aqueous extract faded under exposure to 5000 watts Tungsten Lamp after 48 hours but showed excellent fastness to rubbing. The extract induced excellent brownish colouration in the paint which maintained excellent, opacity, adhesion and good water resistance.Â Â Â